Tissue transglutaminase expression in duodenal mucosa of patients with celiac disease and of normal subjects - İlyas TUNCER and İrfan BAYRAM and İsmet KABA and Rıdvan MERCAN and Serdar UĞRAŞ (Turkish Journal of Gastroenterology, 2019)
-